Comment on Alfassam et al. Development of a Colorimetric Tool for SARS-CoV-2 and Other Respiratory Viruses Detection Using Sialic Acid Fabricated Gold Nanoparticles. Pharmaceutics 2021, 13, 502 - Milad Zandi; Saber Soltani (Pharmaceutics, 2022)
In a published article in Pharmaceutics, researchers developed a sialic acid (SA) stabilized Au nanoparticle system based on SA’s binding ability that exists on the surface of lungs epithelial cells. The authors reported that many respiratory viruses including influenza, Middle-East respiratory syndrome (MERS-CoV), and the current coronavirus (SARS-CoV-2) bind to SA as one of the main binding targets of the surface protein hemagglutinin (HA).